INTEGRATED CURRICULUM IMPLEMENTATION MANAGEMENT AT BOARDING SCHOOL - Abdul Muhyi Alawiy Athallah; Muarif Muarif; Didi Suprijadi; Shofie Nurul Azizah (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
This study is aimed to describe the integrated curriculum implementation management at SMP An-Naja Boarding School West Bandung through planning, implementing, and evaluating the curriculum. The qualitative case study method is used in this investigation. Interviews, observation, and documentation were used to gather the information for this study. Data analysis was carried out using data reduction techniques, then presented the findings and a conclusion. Checking the validity of the data is done through data triangulation. The SMPAn-Naja Boarding School West Bandung study shows that integrated curriculum implementation management is done quite well through some steps; 1) planning of integrated curriculum is done by determining the curriculum objectives and arranging the organization of curriculum contents; 2) Implemented the integrated curriculum by implementing curriculum programs and curriculum supervision; 3) Evaluation of integrated curriculum is done by educational system evaluation model that contains input, process, and products.